An Integrated Approach to Faculty Training and Development-A Case Study - Bhattacharya, S. K. (Journal of Engineering Education Transformations, 2006)
Shortage of good faculty in most of the technical institutions has become a major factor affecting the quality of education and training offered by these institutions. Efforts are being made by AICTE to create training facilities f or the teachers at different locations. However, there has been low internal motivation in the management of most of the institutions towards faculty training. The training programmes conducted by various training institutions have also their limitations in respect of their duration, lack of follow up of training at institution level, no objective evaluation of outcome of training. etc. This paper highlights the initiatives taken by the Management of a Progressive Technical and other Professional Education group towards Faculty Training and Development by allocating a certain percentage of their revenue, with a view to provide quality assurance to the stake holders as also create examples for others to follow.